Principles Of Insect Behaviour - Awasthi, V.B.; Aswathi W..B. (Jodhpur Scientific publishers, 2001)
this book is useful to the students of entomology
kineses menotaxis social wasps long legs
Keywords: kineses,social wasps,long legs